Changes in health insurance coverage, access to care, and health services utilization by sexual minority status in the United States, 2013‐2018. (30th September 2020) - Gonzales, Gilbert; Henning‐Smith, Carrie; Ehrenfeld, Jesse M.
Abstract: Objective: To examine the changes in health insurance coverage, access to care, and health services utilization among nonelderly sexual minority and heterosexual adults between pooled years 2013‐2014 and 2017‐2018. Data Sources: Data on 3223 sexual minorities (lesbians, gay men, bisexual individuals, and other nonheterosexual populations) and 86 181 heterosexuals aged 18‐64 years were obtained from the 2013, 2014, 2017, and 2018 National Health Interview Surveys. Study Design: Unadjusted and regression‐adjusted estimates compared changes in health insurance status, access to care, and health services utilization for nonelderly adults by sexual minority status. Regression‐adjusted changes were obtained from logistic regression models controlling for demographic and socioeconomic characteristics. Principal Findings: Uninsurance declined for both sexual minority adults (5 percentage points, P < .05) and heterosexual adults (2.5 percentage points, P < .001) between 2013‐2014 and 2017‐2018. Reductions in uninsurance for sexual minority and heterosexual adults were associated with increases in Medicaid coverage. Sexual minority and heterosexual adults were also less likely to report unmet medical care in 2017‐2018 compared with 2013‐2014. Low‐income adults (regardless of sexual minority status) experienced relatively large increases in Medicaid coverage and substantial improvements in access to care over the study period. The gains in coverage and access to care across the study period were generally similar for heterosexual and sexual minority adults. Conclusions: Sexual minority and heterosexual adults have experienced improvements in health insurance coverage and access to care in recent years. Ongoing health equity research and public health initiatives should continue to monitor health care access and the potential benefits of recent health insurance expansions by sexual orientation and sexual minority status when possible.